Charakteristika soderžanija pokazatelej sorevnovatel'noj dejatel'nosti boksera v poedinkach s razlicnoj stepen'ju konkurentnosti - Senchukova, H. I.; Kleshcheva, T. V.; Lima, O. T. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
The paper presents a characteristic of the content of indicators of competitive activity of highly qualified boxers in fights with varying degrees of competitiveness, which was determined by evaluating the results of the battle by side judges. The analysis was based on a comparison of competitive battles and battles much less competitive. The quantitative indicators of diabetes in the same athlete were compared in more or less competitive fights. The smaller the difference in the ratio of strikes delivered and missed by opposing boxers, the higher the competitiveness of this fight was recognized. According to our data, two main areas of training highly qualified boxers can be distinguished. The first direction is the study of typical actions and opposition to them. The second direction is the improvement of the ability to meaningfully and correctly act in non-standard combat situations, when the role of a person`s ability to adequately adapt to unexpected changes during a fight greatly increases. Based on the results of our study, we determined the actions of boxers, the most frequently and effectively used in connection with the degree of competitiveness of the fight. The most popular technical actions of boxers of the highest skill level and typical techniquesin their military operations were also highlighted. The boxer`s actions are also divided into situational and standard, pre-planned. The data obtained are considered as a condition for increasing the degree of effectiveness of preparation for competitions. On this basis, training programs for both a single lesson and a long training period can be built